2015
DOI: 10.1111/joic.12214
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Closure of Atrial Septal Defects Under Transthoracic Echocardiography Guidance Without Fluoroscopy or Intubation in Children

Abstract: Percutaneous ASD closure with TTE guidance as the only imaging tool avoids fluoroscopy, endotracheal intubation, and probe insertion and is associated with a satisfactory procedural success rate and lower costs. This procedure is a safe and reliable treatment for ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…We posited that the latter echocardiography guidance option also should be encouraged for all patients to avoid the detrimental radiation exposure of both doctors and patients, reduce cost, and allow adaptation to an outpatient procedure. Percutaneous And Non‐fluoroscopic procedure (PAN procedure) for atrial septal defect (ASD), patent ductus arteriosus (PDA), pulmonary stenosis(PS), and ventricular septal defect(VSD) are routinely performed at our center using echocardiography as the only imaging tool . Early experiences of echo‐guided percutaneous treatments helped us to successfully perform nonfluoroscopy‐guided PBMV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We posited that the latter echocardiography guidance option also should be encouraged for all patients to avoid the detrimental radiation exposure of both doctors and patients, reduce cost, and allow adaptation to an outpatient procedure. Percutaneous And Non‐fluoroscopic procedure (PAN procedure) for atrial septal defect (ASD), patent ductus arteriosus (PDA), pulmonary stenosis(PS), and ventricular septal defect(VSD) are routinely performed at our center using echocardiography as the only imaging tool . Early experiences of echo‐guided percutaneous treatments helped us to successfully perform nonfluoroscopy‐guided PBMV.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous And Non-fluoroscopic procedure (PAN procedure) for atrial septal defect (ASD), patent ductus arteriosus (PDA), pulmonary stenosis(PS), and ventricular septal defect(VSD) are routinely performed at our center using echocardiography as the only imaging tool. [13][14][15][16] Early experiences of echo-guided percutaneous treatments helped us to successfully perform nonfluoroscopyguided PBMV.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous PDA occlusion was first described more than three decades ago and has become the procedure of choice. In recent years, with the extensive use of echocardiography for patient selection and guidance during intervention procedures, echocardiography has become an important tool to improve percutaneous interventional procedures . With increasing operator experience and the development of devices, x‐ray exposure and contrast agents use are minimized largely.…”
Section: Discussionmentioning
confidence: 99%
“…As Ewert et al reported transcatheter closure of atrial septal defects under transesophageal echocardiography without fluoroscopy in 2000, many centers explored to perform transcatheter procedures without fluoroscopy, few succeed. We have reported percutaneous closure of atrial septal defects under transthoracic echocardiographic guidance in 60 patients with satisfactory outcomes . Recently, transthoracic echocardiography (TTE) was used during transcatheter occlusion of PDA to reduce potential injury related to fluoroscopy and angiography .…”
mentioning
confidence: 99%
“…Pan et al have admirably performed percutaneous closure of atrial septal defects (ASD) under transthoracic echocardiography (TTE) guidance without fluoroscopy or intubation in children. Their work is commendable considering the high success rate even with TTE.…”
mentioning
confidence: 99%